2005
DOI: 10.1121/1.4787941
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear frequency dependence of the effective seabottom acoustic attenuation from low-frequency field measurements in shallow water

Abstract: Hamilton’s seabed geo-acoustic model, which is widely accepted, predicts that the attenuation of sound in marine sediments increases linearly with frequency over the full frequency range of interest in ocean acoustics (a few hertz to megahertz). However, Biot-Stoll’s physics-based seabed geo-acoustic model predicts that the bottom attenuation should exhibit non-linear frequency dependence, particularly in sandy bottoms. Since the publication of previous papers [Zhou, J. Acoust. Soc. Am. 78, 1003–1009 (1985); K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…The attenuation at 1kHz was assumed to be consistent with Hamilton's value at that frequency and the density was assumed constant at the measured grab sample value of 1. . Iterative comparison of the measured to calculated transmission loss while adjusting the frequency dependent attenuation revealed that the best fit of attenuation over all frequencies was 7g /cm This compares with a summary by Zhou [2] drawn from a larger and less restrictive group of experimental results yielded α( f o ) = 0.34; n = 1.84 where the reference frequency is not specified.…”
Section: Figure 1: the Nantucket Sound Experimentssupporting
confidence: 56%
See 1 more Smart Citation
“…The attenuation at 1kHz was assumed to be consistent with Hamilton's value at that frequency and the density was assumed constant at the measured grab sample value of 1. . Iterative comparison of the measured to calculated transmission loss while adjusting the frequency dependent attenuation revealed that the best fit of attenuation over all frequencies was 7g /cm This compares with a summary by Zhou [2] drawn from a larger and less restrictive group of experimental results yielded α( f o ) = 0.34; n = 1.84 where the reference frequency is not specified.…”
Section: Figure 1: the Nantucket Sound Experimentssupporting
confidence: 56%
“…
LONG-TERM GOALSOne research goal developed from conducted shallow water (SW) acoustic transmission experiments in sandy-silty areas [1] revealed a nonlinear power law frequency-dependent attenuation at lower frequencies consistent with results reviewed in [2,3] and the observations by the ONR-HEP program. The Biot Theory [4] predicts that sandy sediment attenuation should have a quadratic dependence, however the nonlinear dependence observed was closer to a 1.8 power law most likely due to modal effects.
…”
mentioning
confidence: 75%
“…This result is different from Zhou's model only in the value of the constant factor. 40 The p-wave sound speed is slightly higher at the lower frequency band. This is most likely due to the deeper penetration depth of the lower frequency sound wave, and consequently samples the higher sound speeds in the deeper layers.…”
Section: Bayesian Inversion Resultsmentioning
confidence: 97%
“…Another review by Holmes and Dediu compared the frequency dependent exponent and critical angles reported by various measurements over silty-sands as well the experimental methods used [40]. More recently, Zhou reviewed many previous at sea experimental works and found that some used incorrect depth dependence, thus resulting in incorrect frequency dependence [41]. Zhou corrected the mistakes and came up with a best fit for sandy-silty sediments of where Zhou took the reference frequency f 0 to be 1 kHz.…”
Section: Historical Prospective 121 Attenuation In Sedimentsmentioning
confidence: 99%
“…< T L P E > R is calculated using PE with the geo-acoustic model described above assuming an initial guess for attenuation of K f 0 = 0.34 db/m at the surface at the reference frequency. This initial guess is based on the attenuation at 1kHz reported in reference [41].…”
Section: Frequency Dependence Of Attenuationmentioning
confidence: 99%